(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In recent few years, the researchers are investigating many generalization and extension of special functions because of their applicability in various fields of study especially in mathematical modeling. Keeping in view some summations involving generalized Meijer G-functions in k-form for different combination of parameters have been investigated in this paper. By using contour integral approach and generalized hypergeometric k-functions we derived some new relations and identities. By taking k = 1, we can obtain the classical form of the derived results. Some important applications of generalized Meijer G-functions to the generalized hypergeometric functions have also been considered. The main objective of this paper is to give some useful computational techniques to tackle with the applications related to generalized Meijer G-functions in different mathematical and physical problems, also connect them with some generalized special functions.